A framework for identifying accounting characteristics for asset pricing models, with an evaluation of book‐to‐price. (17th April 2018) - Penman, Stephen H.; Reggiani, Francesco; Richardson, Scott A.; Tuna, İrem
Abstract: We provide a framework for identifying accounting numbers that indicate risk and expected return. Under specified accounting conditions for measuring earnings and book value, book‐to‐price (B/P) indicates expected returns, providing justification for B/P in asset pricing models. However, the framework also points to earnings‐to‐price (E/P) as a risk characteristic. Indeed, E/P, rather than B/P, is the relevant characteristic when there is no expected earnings growth, but the weight shifts to B/P with growth. Using this framework we resolve a puzzle: in contrast to previous empirical research, we find that leverage is positively associated with future returns, as predicted by theory.